Guselkumab Treatment Outcomes and Persistence in a Nationwide Real-world Cohort of Patients with Plaque Psoriasis - Mälkönen Tarja; Nuutinen Pauliina; Hallinen Taru; Soini Erkki; Nissinen Riikka; Wennerstöm Christina; Rantanen Tapio; Hagman Johanna H.; Harvima Rauno; Höök-Nikanne Johanna; Ilves Tiina; Lintu Päivi; et al. (Medical Journals/Acta D-V, 2022)
Guselkumab treatment outcomes and persistence were assessed in a real-world cohort of Finnish patients with difficult-to-treat plaque psoriasis over a median follow-up of 1 year. Data on 181 patients who initiated guselkumab at the 15 study centres were collected retrospectively from the patient charts. Prior exposure to biologic therapies was common, with 56% and 35% having used at least 1 and 2 biologics, respectively. Median guselkumab treatment duration was 11 months with 21 patients (12%) discontinuing treatment during follow-up. Of 85 patients with a follow-up duration of at least 1 year, 73 (86%) were still on guselkumab at 1 year. Significant improvements during follow-up were seen in the absolute Psoriasis Area and Severity Index (PASI) scores with 32 patients (80%) having absolute PASI ≤ 2 after a 9–14-month treatment. Guselkumab treatment was effective and treatment persistence was high in the nationwide Finnish real-life setting.